2017
DOI: 10.1103/physrevlett.119.151801
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Unified Resolution to RK(*) and R(D(<

Abstract: It is a challenging task to explain, in terms of a simple and compelling new physics scenario, the intriguing discrepancies between the standard model expectations and the data for the neutralcurrent observables RK and RK * , as well as the charged-current observables R(D) and R(D * ). We show that this can be achieved in an effective theory with only two unknown parameters. In addition, this class of models predicts some interesting signatures in the context of both B decays as well as high-energy collisions.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
47
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 66 publications
1
47
0
Order By: Relevance
“…A typical case of how crucial the invisible channel can be for the explanation of the apparent anoma-lies in the semileptonic decays of the B meson has been exemplified in Ref. [3] As an example of what we have just said, let us note that apart from neutrinos coming from non-SM operators, the FCNC transition b → s can involve light invisible scalars in the final state. If they are singlet under all the SM gauge groups, they can very well be a candidate for cold dark matter (DM).…”
Section: Introductionmentioning
confidence: 88%
“…A typical case of how crucial the invisible channel can be for the explanation of the apparent anoma-lies in the semileptonic decays of the B meson has been exemplified in Ref. [3] As an example of what we have just said, let us note that apart from neutrinos coming from non-SM operators, the FCNC transition b → s can involve light invisible scalars in the final state. If they are singlet under all the SM gauge groups, they can very well be a candidate for cold dark matter (DM).…”
Section: Introductionmentioning
confidence: 88%
“…It is thus desirable to consider which BSM constructions could be at the origin of these effective operators. Among the most minimal scenarios studied, one has flavour-sensitive Z exchanges [37][38][39][40][41][42][43][44][45][46][47][48][49][50], leptoquark exchanges , R−parity violating supersymmetric models [76][77][78][79][80][81], and various other constructions [82][83][84][85][86][87][88][89][90][91].…”
Section: Introductionmentioning
confidence: 99%
“…In the present case, instead of attempting a generic study, we consider a particular signature, at the LHC, prompted by the scenarios discussed in Refs. [1,2]. Some such studies have been attempted in the past, but in entirely different contexts, both at the simulation level [53][54][55][56][57][58][59][60], as well as by the ATLAS and CMS collaborations who have searched for flavor violating signatures with dilepton final states [61][62][63][64][65][66].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies (Refs. [1,2]) have shown that a class of effective field theory (EFT) models may explain such anomalies in terms of only a few parameters which can be determined phenomenologically. In this literature, we examine such resolutions in the context of the requisite (s b)(τ τ ) operator, and look for its signals at the 13 TeV LHC, with a final state of one b-jet, and an oppositely charged µ-τ pair, with the muon coming from the decay of one of the τ leptons.…”
mentioning
confidence: 99%